The effect of breaches of the psychological contract on the job satisfaction and wellbeing of doctors in Ireland: a quantitative study - Aedin Collins; Alexandra Beauregard (BMC, 2020)
Abstract Background Medicine is one of the most popular college degrees at both undergraduate and postgraduate level. Despite this, morale and wellbeing in doctors at all levels internationally is reportedly low. Long hours and stressful working environments have been implicated as the cause of this. The psychological contract is the implicit expectations and mutual obligations held between an employee and employer. Breaches in this contract can lead to strong negative emotional responses. This study will examine the psychological contract of non-consultant doctors and gain further insight into their job satisfaction and wellbeing. It aims to ascertain the effect of breaches of the psychological contract on their job satisfaction and wellbeing. Methods This is a quantitative study performed using a questionnaire on a closed online forum. Job satisfaction, wellbeing and breaches of the psychological contract were measured using pre-existing and pre-validated scales. Statistical analysis was performed to determine the effect of breaches of the psychological contract on job satisfaction and wellbeing. Results This study ascertained that training and career development were the most important areas of the psychological contract for non-consultant doctors and training and organizational support the most important breaches. It found, overall, positive levels of job satisfaction and wellbeing. A statistically significant relationship between breaches of the psychological contract and job satisfaction and wellbeing was found. Conclusion This study provides an insight into the psychological contract of non-consultant doctors in Ireland. By doing so, it identifies areas for change which may improve their future job satisfaction and wellbeing.